Type 2 Diabetic Mellitus Inhibits Skin Renewal through Inhibiting WNT-Dependent Lgr5+ Hair Follicle Stem Cell Activation in C57BL/6 Mice - Minghui Wang; Shangsheng Yao; Dehua He; Mulan Qahar; Jinqing He; Meifang Yin; Jun Wu; Guang Yang (Journal of Diabetes Research)
Background. Hair follicles are important accessory organs of the skin, and it is important for skin renewal and performs variety of important functions. Diabetes can cause several dermatoses; however, its effect on hair follicles is unclear. The purpose of this study was to investigate the effect of type II diabetes (T2DM) on the hair follicles of mice. Methods. Seven-week-old male C57BL/6 littermate mice were divided into two groups. The treatment group was injected with streptozotocin (STZ) to induce T2DM, and the control group was parallelly injected with the same dose of buffer. Seven days after injection, the back is depilated to observe the hair follicle regeneration. Hair follicle regeneration was observed by naked eyes and HE staining. The proliferation of the skin cells was observed by PCNA and K14 staining. The altered genes were screened by RNA sequencing and verified by qRT-PCR. In addition, Lgr5 + GFP/mTmG transgenic mice were used to observe the effect of T2DM on Lgr5 hair follicle stem cells (HFSC). And the expression of WNT4 and WNT8A were measured by Western Blot. Results. T2DM inhibited hair follicle regeneration. Compared to control mice, T2DM mice had smaller hair follicles, reduced skin thickness, and less expression of PCNA and K14. RNA sequencing showed that the two groups had significant differences in cell cycle and proliferation-related pathways. Compared with the control mice, the mRNA expression of Lgr4, Lgr5, Wnt4, and Wnt8a was decreased in the T2DM group. Moreover, T2DM inhibited the activation of Lgr5 HFSC and the expression of WNT4 and WNT8A. Conclusions. T2DM inhibited hair follicle regeneration and skin cells proliferation by inhibiting WNT-dependent Lgr5 HFSC activation. This may be an important reason for the reduction of skin renewal ability and the formation of chronic wounds caused by diabetes. It is important for the treatment of chronic diabetic wounds and the development of tissue engineering.